Pengaruh Atraksi Wisata Kuliner terhadap Minat Berwisata Masyarakat melalui Social Media Marketing TikTok di Daerah Istimewa Yogyakarta - Melvern, Melvern; Evangeline, Laura; Wijaya, Verina (Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the influence of culinary tourism attractions on people's interest in traveling in the Special Region of Yogyakarta through social media marketing on TikTok. The approach used is quantitative with a survey method, involving 115 respondents who are interested in culinary tourism in Yogyakarta. Data were collected through questionnaires and analyzed using SmartPLS to test the relationship between variables. The results of the study indicate that culinary tourism attractions have a significant effect on people's interest in traveling, both directly and through social media, especially TikTok. The uniqueness of local culinary such as gudeg and bakpia, as well as the authentic experiences offered, have succeeded in creating viral content that strengthens tourist interest. Social media marketing, especially TikTok content, has proven effective in promoting local culinary tourism and increasing interest in visiting. Based on these findings, it is recommended that culinary business actors introduce more interactive experiences, such as involving tourists in making culinary, and offering attractive promos through TikTok to increase transactions. In addition, content creators need to pay attention to the context and attractive visuals in making videos in order to more effectively reach the right audience. This study provides an important contribution to the development of social media-based culinary tourism promotion strategies in Yogyakarta. Keywords: culinary tourism, travel interest, social media, TikTok